Design and performance analysis of multiple transmitters/receivers on Free Space Optics(FSO) link - Md. Noor, Nur Haedzerin; Naji, Ahmed Wathik; Al-Khateeb, Wajdi Fawzi Mohammed (IIUM Press, 2011)
Free Space Optics is the concept of transmitting very high bandwidth information using the optical beam from one point to another through the atmosphere. This technology offers various advantages to both telecommunication users and providers. It provides a high data rates up to several Gbps, has immunity to radio frequency interferences, requires no licensing, gives a highly secured communication link due to the usage of a very narrow beam angle, and offers an inexpensive, fast and easy deployment when compared to the fiber optic installation